Aspectos procesales relativos al daño ambiental en el Ecuador - René Bedón Garzón (Ius Humani. Jornal do direito, 2010)
This paper aims to determine, through a deep analysis of different doctrines, the definition of environmental damage; it also seeks to determine the difference between damage to nature and the civil environmental damage, which is damage to individual interests or collective environmental event occasion. To this purpose, we intend to study certain procedural rules and case law concerning Ecuadorian environmental management, also in comparative law considers how countries like Chile, Spain and Argentina regulate compensation and repair environment.